Evaluation of a specific reaction and action speed test for the soccer goalkeeper - Knoop, M.; Fernandez-Fernandez, J.; Ferrauti, A. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to develop and evaluate a new test for the soccer goalkeeper that involved perceptual and movement response components (i.e., sprint running, jumping, diving, and direction changing). The evaluation consisted of measurements in different age (U19 [18.0 ± 0.9 years], n = 21; U14 [14.1 ± 0.3 years], n = 13) and performance (i.e., first goalkeepers and substitutes) groups of goalkeepers, including measures of test-retest reliability. Validity was assessed comparing the 2 groups of goalkeepers with different expertise levels (i.e., competitive level and age group). The test-retest correlations of the reaction and action speed (RAS) test performance were significant in all single (intraclass correlation coefficient [ICC] = 0.68-0.95; p < 0.01) and complex measurements (ICC = 0.91; p < 0.01). The RAS single test performance was higher in older (U19) compared with in younger (U14) players (p < 0.001), and they also showed better results in the RAS complex tests (p = 0.000), being significantly different between the first goalkeepers and their substitutes (p = 0.001). Moreover, for all age groups (i.e., U14, U19), defensive actions to the bottom corners were faster than those to the top corners, with large ES (i.e., > 1). The major findings of the study were that the RAS test provided a reliable and valid method of assessing specific defensive agility in a group of youth soccer goalkeepers. Performance responses during the RAS test allow coaches to discriminate between age-matched goalkeepers, identify weaknesses (e.g., nonpreferred side dive performance), and to design specific training tasks.